Sleep patterns modify the association of 25(OH)D with poor cardiovascular health in pregnant women - Yin, Wan-jun; Yu, Li-jun; Wang, Peng; Tao, Rui-xue; Jiang, Xiao-min; Zhang, Ying; Zhu, Dao-min; Zhu, Peng (Frontiers in Nutrition, 2022)
Background The relationship between vitamin D status and gestational cardiovascular health (CVH) is inconsistent in previous studies. Emerging evidence shows that sleep behaviors are related to vitamin D metabolism. However, no studies evaluate the interaction of vitamin D and sleep behaviors on gestational CVH. Objective We aimed to estimate the relationship between 25-hydroxyvitamin D [25(OH)D] concentrations and gestational CVH, and whether the relationship was modified by sleep behaviors. Methods The data of this study was from a multicenter birth cohort study. A total of 9,209 pregnant women at 16–23 weeks of gestation were included. 25(OH)D concentrations were measured from collected blood. Sleep patterns consisted of major sleep behaviors including duration, chronotype, insomnia, snoring, and excessive daytime sleepiness. Data on poor CVH was based on four “clinical” CVH metrics, including body mass index, blood pressure, total cholesterol, and glucose levels. Results The proportion of women with poor CVH was 25.0%. The relative risk (RR) (95%CI) of poor CVH was 0.67 (0.58–0.76) in women with 25(OH)D ≥ 50 nmol/L after multivariate adjustments. Lower 25(OH)D concentrations were significantly associated with poor CVH. Such association was also evident in subgroups analysis. We found a significant interaction of 25(OH)D (P for interaction = 0.01) with sleep patterns on the risk of poor CVH. A negative dose-response relation was observed between 25(OH)D concentrations and poor CVH risk in healthy or intermediate sleep, not poor sleep. 25(OH)D concentrations were lower and the risk of poor CVH was higher in pregnant women with poor sleep patterns (P < 0.05). Conclusion Our study suggests that sleep patterns modify the association of 25(OH)D concentrations with the CVH among pregnant women.